2009
DOI: 10.1177/1352458509106851
|View full text |Cite
|
Sign up to set email alerts
|

Antiacquaporin 4 antibodies detection by different techniques in neuromyelitis optica patients

Abstract: Detection of NMO-IgG or anti-AQP4 antibodies may represent a valuable tool to assist neurologists in the differential diagnosis between patients with NMO, hrNMO, APTM, or MS. The current lack of a gold standard to detect anti-AQP4 antibodies implies the necessity to standardize the detection of these antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 29 publications
1
55
0
Order By: Relevance
“…The presence of oligoclonal bands (OCB) of immunoglobulin G (IgG) restricted to the CSF is detected in only 15-30% of the patients [1]. The detection of AQP4-IgG is considered a serum biomarker [7,8] contributing to the diagnosis of NMO and to broaden its clinical spectrum. However, the AQP4-IgG seropositive rate depends on the assay type used [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of oligoclonal bands (OCB) of immunoglobulin G (IgG) restricted to the CSF is detected in only 15-30% of the patients [1]. The detection of AQP4-IgG is considered a serum biomarker [7,8] contributing to the diagnosis of NMO and to broaden its clinical spectrum. However, the AQP4-IgG seropositive rate depends on the assay type used [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The detection of AQP4-IgG is considered a serum biomarker [7,8] contributing to the diagnosis of NMO and to broaden its clinical spectrum. However, the AQP4-IgG seropositive rate depends on the assay type used [8][9][10][11]. The cellbased assay, currently the gold standard, has 100% specificity and between 68% (commercial CBA) and 73% (Oxford CBA) sensitivity in contrast with the commercial ELISA assay that has 97.7% specificity and 70% sensitivity [11].…”
Section: Introductionmentioning
confidence: 99%
“…This has been confirmed in many studies, and the presence of such antibodies is now among the diagnostic criteria for NMO 5,6 .…”
Section: Discussionmentioning
confidence: 59%
“…A specific IgG autoantibody, NMO-IgG, selectively targeting aquaporin 4 (AQP4), which accumulates in the central nervous system (CNS) microvessels, pia, subpia, and Virchow-Robin space, has been confirmed by indirect immunofluorescence with a composite substrate of mouse tissue 3,4 . According to this antibody, the new diagnostic criteria for NMO proposed by Wingerchuk et al facilitate its distinction from multiple sclerosis (MS) 5,6 . In subsequent studies, analysis of pathological brain lesions in NMO patients revealed a pattern of vasculocentric immune complex deposition and AQP4 loss ORIGINAL ARTICLE identical to that seen in NMO lesions, suggesting that AQP4 antibodies are related to NMO pathology 7,8 .…”
mentioning
confidence: 99%
“…In the diagnosis section NMO-DBr takes into account the sensitivity variability of the AQP4 antibody assays [31][32][33][34][35][36] and the typical lesions which have been described on brain MRI 10,[12][13][14][15]24 . In addition to choices within the widely accepted NMO spectrum disorders 2,6 the system includes patients with formes frustres of NMO, typical lesions of NMO on brain MRI and AQP4-antibody seronegativity; and those who have brainstem syndrome, hypothalamic syndrome, or symptoms of encephalopathy in association typical lesions of NMO on brain MRI or AQP4-antibody seropositivity.…”
Section: Resultsmentioning
confidence: 99%